Repeat hepatectomy for recurrent colorectal metastases. Issue 6 (12th March 2013) - Wicherts, D. A.; de Haas, R. J.; Salloum, C.; Andreani, P.; Pascal, G.; Sotirov, D.; Adam, R.; Castaing, D.; Azoulay, D.
Abstract : Best chance of survival if suitable for repeat surgery Abstract : Background: The oncological benefit of repeat hepatectomy for patients with recurrent colorectal metastases is not yet proven. This study assessed the value of repeat hepatectomy for these patients within current multidisciplinary treatment. Methods: Consecutive patients treated by repeat hepatectomy for colorectal metastases between January 1990 and January 2010 were included. Patients undergoing two‐stage hepatectomy were excluded. Postoperative outcome was analysed and compared with that of patients who had only a single hepatectomy. Results: A total of 1036 patients underwent 1454 hepatectomies for colorectal metastases. Of these, 288 patients had 362 repeat hepatectomies for recurrent metastases. Some 225 patients (78·1 per cent) had two hepatectomies, 52 (18·1 per cent) had three hepatectomies, and 11 patients (3·8 per cent) had a fourth hepatectomy. Postoperative morbidity following repeat hepatectomy was similar to that after initial liver resection (27·1 per cent after first, 34·4 per cent after second and 33·3 per cent after third hepatectomy) ( P  = 0·069). The postoperative mortality rate was 3·1 per cent after repeat hepatectomy versus 1·6 per cent after first hepatectomy. Three‐ and 5‐year overall survival rates following first hepatectomy in patients who underwent repeat hepatectomy were 76 and 54 per cent respectively, compared with 58 and 45 per cent in patients who had only one hepatectomy ( P  = 0·003). In multivariable analysis, repeat hepatectomy performed between 2000 and 2010 was the sole independent factor associated with longer overall survival. Conclusion: Repeat hepatectomy for recurrent colorectal metastases offers long‐term survival in selected patients.